The Impact of COVID-19 on Foreign Investors : Evidence from the Second Round of a Global Pulse Survey - Saurav, Abhishek; Kusek, Peter; Kuo, Ryan; Viney, Brody (World Bank, Washington, DC, 2020)
The COVID-19 pandemic has had a profound impact on the global economy, triggering the deepest global recession of the past eight decades. Together, the crisis and public health response have caused both a severe supply shock in the form of reduced worker availability and supply chaindisruptions, and a massive demand shock as consumption became restricted and confidence fell. The World Bank forecasts a 5.2 percent contraction in global GDP in 2020, including a 2.5 percent decline in emerging markets and developing economies (World Bank 2020).